1987
DOI: 10.1002/actp.1987.010380504
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on molecular associations in solid and liquid phases of aqueous solutions. I. Topoenergetic representation of the behaviour of several sulphates

Abstract: The previously obtained results on sulphate‐water interactions both in liquid and solid states in the four measuring systems (high resolution mixing calorimetry, differntial scanning calorimetry, thermomechanical analysis, and dynamic thermal densimetric analysis) are retrieved according to the universal topoenergetic procedure by considering the solute concentration as governing potential. Ontogenic and phylogenic parameters defining the nature, the overall amplitude, the mass of the kinetic entity and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…38 -40 It has been already demonstrated that the morphological changes, which occur by removing 2EH from the macroporous S-DVB copolymers by azeotropic distillation with water, are reversible, the collapsed network being completely re-expanded in a proper solvent (e.g., toluene), and the real porosity was evidenced after the removal of the good solvent with methanol. 38 Such behavior also has been observed for other systems. 9,11,14,17,21 This shows that the whole pore structure of these copolymers is memorized by the copolymer network, 20,23 and a good flexibility of the internuclear chains, which could be a very useful characteristic in the synthesis of some macroporous SBAEs with a high osmotic resistance.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…38 -40 It has been already demonstrated that the morphological changes, which occur by removing 2EH from the macroporous S-DVB copolymers by azeotropic distillation with water, are reversible, the collapsed network being completely re-expanded in a proper solvent (e.g., toluene), and the real porosity was evidenced after the removal of the good solvent with methanol. 38 Such behavior also has been observed for other systems. 9,11,14,17,21 This shows that the whole pore structure of these copolymers is memorized by the copolymer network, 20,23 and a good flexibility of the internuclear chains, which could be a very useful characteristic in the synthesis of some macroporous SBAEs with a high osmotic resistance.…”
Section: Introductionsupporting
confidence: 70%
“…III prepared in the presence of 2EH as porogen with D in the range of 0.45-0.55, always led to a decrease of the specific surface area. 38 A very small decrease of the average pore radius was observed after chloromethylation for the starting copolymers, which had pores with r p 's in the range of 10 -20 nm, prepared at a dilution of D ϭ 0.45 and a high increase of the r p after chloromethylation of macroporous copolymers, as much as the porosity was higher. 38 This showed that the morphological changes determined by the chloromethylation reaction depend both on the chloromethylation reagent and on the copolymer structure.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The most commonly used starting copolymers for obtaining ion exchangers with different functionalities and morphologies are still styrene-divinylbenzene (S-DVB) copolymers. [1][2][3][4] Among functional polymers, linear and crosslinked copolymers bearing primary amine groups are of a great interest because of their high reactivity, which allows the incorporation of numerous additional moieties. [5][6][7][8][9] However, ion exchangers with primary amine groups are difficult to obtain by chemical reactions of S-DVB copolymers.…”
Section: Introductionmentioning
confidence: 99%